Utilization of Vermicompost and Npk Fertilizers on the Growth, Yield, Nutrient and Protein Content of Mung Bean (Vigna Radiata L.) (Journal of Biodiversity Conservation and Bioresource Management, 2023)
A pot experiment was conducted in Soil, Water and Environment department, University of Dhaka, during the late rabi season for 60 days with mung bean plants. The study was cnducted to evaluate the interactive effects of vermicompost and NPK fertilizers on mung bean plants’ growth, yield, nutrient and protein content. The trial was laid out in a completely randomized design (CRD) followed by three replications, having ten treatments, including control. The first four treatments contained vermicompost mixed with soil at the rate of 2, 4, 6, and 8 ton ha-1. The other four treatments contained 50% of N12P22K10 kg ha-1, while a single treatment possesses N25P45K20 kg ha-1. The growth and yield contributing parameters, viz. plant height (30 cm), leaf number (18 plant-1), leaf area (152 cm2), branch number (4 plant-1), weight of seed (4.45 g), yield of fresh (17.81 g) and dry (10.32 g) mung bean plant was found maximum with T10 (vermicompost 8 ton ha-1 + N12P22K10 kg ha-1). The mineral nutrient content N (4.69%), P (0.08%) and K (0.65%) attained the highest in the harvested seed in the same T10. The protein content (29.32%) was also found highest in T10. On the basis of the findings, it may be recommended to use VC 8 ton ha-1 plus N12P22K10 kg ha-1 to cultivate the mung bean in the context of Bangladesh.J. Biodivers. Conserv. Bioresour. Manag. 2023, 9(1): 29-40